2020
DOI: 10.1111/camh.12375
|View full text |Cite
|
Sign up to set email alerts
|

SafeSpot: an innovative app and mental health support package for Scottish schools – a qualitative analysis as part of a mixed methods study

Abstract: AimsThe aim of the study was to investigate teachers’ and pupils’ perceptions about the effect of the SafeSpot mental health curriculum on the well‐being of young people and on their knowledge of mental health conditions. This trial intends to determine the acceptability and benefits of web and mobile technology in delivering emotional well‐being in schools, through use of the SafeSpot programme.BackgroundWith 10% of young people aged 5 to 16 diagnosed with a mental disorder, there is pressure for schools to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…Many studies on mental health awareness programmes points towards the need for expansion of community-based and school-based programmes to spread deliver mental health promotion and awareness generation activities [29,30]. Similar to our study, the qualitative results from a study by Mallika Punnukollu et al, showed that teachers agree that family issues, influence of social media and youth culture are the main reason for stress and other mental health issues [31].…”
Section: Discussionsupporting
confidence: 87%
“…Many studies on mental health awareness programmes points towards the need for expansion of community-based and school-based programmes to spread deliver mental health promotion and awareness generation activities [29,30]. Similar to our study, the qualitative results from a study by Mallika Punnukollu et al, showed that teachers agree that family issues, influence of social media and youth culture are the main reason for stress and other mental health issues [31].…”
Section: Discussionsupporting
confidence: 87%
“…At the same time, primary school teachers can also create an active will quality in their daily work and life, including a high sense of responsibility, tolerance for children, moral quality, vitality, attention, keen observation, and emotional control ability. Therefore, the efficient mental health and mental health culture education ability [19] is as shown in Figure 6 below.…”
Section: Solutions and Strategiesmentioning
confidence: 99%
“…Social identification theory also points out that the decisions made by enterprises affect the employees' attitudes towards enterprises, and organizational identification has a positive impact on employees' behaviors [ 18 , 19 ]. Social responsibility makes employees believe that their enterprises are responsible and enhances employees' recognition of the enterprise.…”
Section: Questionnaire Design and Data Processingmentioning
confidence: 99%
“…Therefore, the control variables are gender, age, education, and posts. This study mainly uses four scales to collect data [ 18 , 22 ]. All measurement scales are scored by the Likert 5 scoring method, and 1–5 points correspond to the options from “total inconformity” to “total conformity,” respectively.…”
Section: Questionnaire Design and Data Processingmentioning
confidence: 99%